Application Theory of Planned Behavior: Determinants of Behavior to Use Personal Protective Equipment among Tobacco Farmers in Temanggung, Central Java: A Multilevel Analysis - Yovita Eka Ratna Kumala; Setyo Sri Rahardjo; Endang Sutisna Sulaeman (Journal of Health Promotion and Behavior, 2020)
Background: Tobacco farmers has the risk of being exposed by wet nicotine during harvesting tobacco leaves or is often called as Green Tobacco Sickness (GTS). GTS prevention can be conducted by using Personal Protective Equipment (PPE) before farmers harvesting tobacco leaves. Behavior in using PPE among farmers is affected by sex types, education, attitude, subjective norm, intention, and perceived behavioral control. The study aims to analyze the determinant of behavior to use PPE among tobacco farmers in Temanggung Regency, Central Java.Subjects and Method: It was a cross sectional study, conducted in 25 villages in Temanggung Regency, August – October 2019.  The sample was a total of 200 tobacco farmers. The sampling technique used was simple random sampling. Dependent variable of the study was behavior to use PPE among tobacco farmers. Independent variables of the study were sex types, education, attitude, subjective norm, intention, and perceived behavioral control. The data collection used was questionnaires and processed by using multilevel multiple logistic regression with Stata 13.Results: The use of PPE among tobacco farmers during harvesting tobacco leaves was increased by male (b= 2.52;  95% CI= 1.39 up to 3.66; p<0.001), education ≥ High School (b= 2.15;  95% CI= 1.10 up to 3.19; p<0.001), strong famers’ intention (b= 1.82;  95% CI= 0.13 up to 2.22; p= 0.027), positive farmers’ attitude (b= 1.63;  95% CI= 0.58 up to 2.68; p= 0.002), supporting subjective norm (b= 1.74;  95% CI= 0.67 up to 2.81; p= 0.001), and strong perceived behavioral control (b= 1.53;  95% CI= 0.52 up to 2.54; p= 0.003).Conclusion: Behavior to use PPE among tobacco farmers is affected by sex types, education, attitude, subjective norm, and perceived behavioral control.Keywords: behavior to use PPE, farmers, theory of planned behaviorCorrespondence: Yovita Eka Ratna Kumala. Master Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia, 57126. Email: yovitakumala19@gmail.com. Mobile: 083867630850Journal of Health Promotion and Behavior (2020), 5(1): 50-58https://doi.org/10.26911/thejhpb.2020.05.01.07